A composite foraminiferal biostratigraphic sequence for the Lower Miocene deposits in the type area of the Qom Formation, central Iran, developed by constrained optimization (CONOP). (January 2017) - Daneshian, Jahanbakhsh; Ramezani Dana, Leila; Sadler, Peter
Abstract: Benthic foraminifera species commonly outnumber planktic species in the type area of the Lower Miocene Qom Formation, in north central Iran, where it records the Tethyan link between the eastern Mediterranean and Indo- Pacific provinces. Because measured sections preserve very different sequences of first and last occurrences of these species, no single section provides a completely suitable baseline for correlation. To resolve this problem, we combined bioevents from three stratigraphic sections into a single composite sequence by constrained optimization (CONOP). The composite section arranges the first and last appearance events (FAD and LAD) of 242 foraminifera in an optimal order that minimizes the implied diachronism between sections. The composite stratigraphic ranges of the planktic foraminifera support a practical biozonation which reveals substantial local changes of accumulation rate during Aquitanian to Burdigalian times. Traditional biozone boundaries emerge little changed but an order of magnitude more correlations can be interpolated. The top of the section at Dobaradar is younger than previously thought and younger than sections at Dochah and Tigheh Reza-Abad. The latter two sections probably extend older into the Aquitanian than the Dobaradar section, but likely include a hiatus near the base of the Burdigalian. The bounding contacts with the Upper Red and Lower Red Formations are shown to be diachronous. Highlights: Foraminifera species in the type area of the Lower Miocene Qom Formation, in north central Iran, based on CONOP investigated. The composite section arranges FAD and LAD of foraminifera. Local changes of accumulation rate considered. Traditional biozone boundaries changed and based on The standard foraminiferal biozone the top of the section at Dobaradar is younger.